Paraneoplastic Conjunctival Acanthosis Nigricans: A Case Report. Issue 3 (24th March 2021) - Huang, Natalie; Yin, Han Y.; Swan, Robert
Abstract : Purpose: To report a patient who presented with red eye and diffuse palpebral conjunctival thickening and papillary growth bilaterally. Methods: A 63-year-old woman with a medical history of stage IV adenocarcinoma of the lung with metastasis to the bone, the lung, and the lymph nodes presented with redness and irritation of both eyes for 3 months. The patient has been treated with topical corticosteroids for 3 weeks with no relief of symptoms. Results: Clinical examination and pathology report of conjunctival biopsy confirmed the diagnosis of conjunctival acanthosis nigricans. Conclusions: Conjunctival acanthosis nigricans is a rare paraneoplastic condition that resembles papilloma and can present a challenge in diagnosis. When acanthosis nigricans occurs after the diagnosis of malignancy, it can be an indicator of progression of the underlying condition. The diagnosis of conjunctival acanthosis nigricans in a patient with no history of cancer should prompt clinicians for further malignancy workup.